PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. AGUNG MOTOR I DI KABUPATEN TABANAN - Putra, I Wayan Arta Permana; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
The purpose of this study was to determine the effect of transformational leadership, motivation and discipline on employee performance. Method of determining the sample in this study using a sample of saturated , whereby the respondent amounted to 47 people . The analysis tool used is multiple linear regression analysis. The results obtained in this study is transformational leadership positive effect on employee performance, motivation positive effect on employee performance and discipline of work has positive influence on employee performance. Leaders should provide good facilities to support the work of employees and provide positive motivation to improve morale and company employees should be put in the right position according to the competence of the employee. Employees should be timely tasks and work in accordance with the company's goals.
Keywords: kepemimpinan transformasional; motivasi; disiplin kerja; kinerja karyawan